Towards resolving the spatial metabolome with unambiguous molecular annotations in complex biological systems by coupling mass spectrometry imaging with structures for lossless ion manipulations. Issue 3 (7th December 2018) - Nagy, Gabe; Veličković, Dusan; Chu, Rosalie K.; Carrell, Alyssa A.; Weston, David J.; Ibrahim, Yehia M.; Anderton, Christopher R.; Smith, Richard D.
Abstract : We demonstrate the coupling of LESA to SLIM SUPER IM-MS for the unambiguous annotation of important isomeric glycoforms in carbon-fixing communities. Abstract : We demonstrate the coupling of liquid extraction surface analysis (LESA) to structures for lossless ion manipulations in conjunction with serpentine ultralong path with extending routing (SLIM SUPER) ion mobility-mass spectrometry (IM-MS) for the unambiguous annotation of important isomeric glycoforms in carbon-fixing communities.